1994
DOI: 10.1203/00006450-199411000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Renal Function in Preterm Neonates

Abstract: The plasma creatinine concentration is elevated at birth and decreases concomitantly with the rapid increase in glomerular filtration rate that occurs in the first postnatal weeks. The velocity of these changes was assessed during the first 3 wk of life of 66 term and preterm infants. The plasma creatinine concentration, creatinine clearance, and sodium fractional excretion were measured serially at weekly intervals, starting 1-4 d after birth [mean = 1.5 -c 0.8 (SD) dl. Premature infants were separated into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
100
3
11

Year Published

1997
1997
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(125 citation statements)
references
References 24 publications
(26 reference statements)
11
100
3
11
Order By: Relevance
“…SeCr increased after birth of the preterm infant, reaching a peak that was at the second day for infants born at 29 to 31 weeks of GA and at the fifth day for those born at p28 weeks of GA. SeCr peak was found to be higher for lower GA. Our results are consistent with others: Bueva and Guignard 18 showed a negative correlation between plasma creatinine and GA in one study comparing preterm infants versus term infants between the first and the second day of life; Gallini et al 5 found that during the first week of life, the maximum value of SeCr was significantly higher for GA lower than 27 weeks than for 27 to 28, 29 to 30 and 31 to 32 weeks GA; recently Auron and Mhanna 6 showed that in VLBW infants younger than 29 weeks or smaller than 1000 g there was a delay in the decrease of their SeCr that extended beyond the first day of life. So, gestation and age-based reference charts have been proposed for the interpretation of creatinine values in extremely premature babies <28 weeks GA. 21 Our study also disclosed EOS, RDS and ibuprofen-treated hsPDA as other independent factors associated with high postnatal SeCr increase.…”
Section: Discussionsupporting
confidence: 94%
“…SeCr increased after birth of the preterm infant, reaching a peak that was at the second day for infants born at 29 to 31 weeks of GA and at the fifth day for those born at p28 weeks of GA. SeCr peak was found to be higher for lower GA. Our results are consistent with others: Bueva and Guignard 18 showed a negative correlation between plasma creatinine and GA in one study comparing preterm infants versus term infants between the first and the second day of life; Gallini et al 5 found that during the first week of life, the maximum value of SeCr was significantly higher for GA lower than 27 weeks than for 27 to 28, 29 to 30 and 31 to 32 weeks GA; recently Auron and Mhanna 6 showed that in VLBW infants younger than 29 weeks or smaller than 1000 g there was a delay in the decrease of their SeCr that extended beyond the first day of life. So, gestation and age-based reference charts have been proposed for the interpretation of creatinine values in extremely premature babies <28 weeks GA. 21 Our study also disclosed EOS, RDS and ibuprofen-treated hsPDA as other independent factors associated with high postnatal SeCr increase.…”
Section: Discussionsupporting
confidence: 94%
“…The fifth day of life was chosen to study the relationship between SCr and GA or BW because SCr reached a plateau between the fourth and sixth day of life. Our findings are consistent with others; Bueva et al 14 have shown in 11 patients (1001 to 1500 g) a decrease in SCr between day 1 to 2 and 8 to 9 (from 95±5 to 64±5 mmol/l, respectively).…”
Section: Discussionsupporting
confidence: 94%
“…2 Others have also reported reduced GFR values during the first 48 h of life secondary to the inability of premature kidneys to clear high SCr values. 3,14 To determine the relationship between SCr and GA, and SCr and BW in VLBW infants, SCr values of all VLBW infants were studied during their first days of life. The fifth day of life was chosen to study the relationship between SCr and GA or BW because SCr reached a plateau between the fourth and sixth day of life.…”
Section: Discussionmentioning
confidence: 99%
“…In preterm neonates glomerular filtration rate (GFR) is very low at birth, and does not rise as rapidly as full term infants during the neonatal period [20,21]. As expected, glomerular filtration rate has shown to increase more rapidly after 34 weeks gestation [22,23] which coincides with the timing of the completion of nephrogenesis.…”
Section: Renal Functionmentioning
confidence: 83%
“…During the first week after birth, glomerular filtration rate (GFR) is significantly lower in preterm infants compared to term infants [26][27][28] and it is positively correlated with gestational age at birth and postnatal age [29][30][31]. Likewise, creatinine clearance, one of the most commonly used markers of renal function, is positively correlated with both gestational age and postnatal age [20,21,[29][30][31][32][33][34][35][36][37][38][39]. In addition, preterm neonates excrete high amounts of sodium in the early neonatal period compared to term neonates, with the fractional excretion of sodium inversely correlated with gestational age and postnatal age [29,[39][40][41][42][43].…”
Section: Renal Functionmentioning
confidence: 96%